2017
DOI: 10.1016/j.redox.2017.03.029
|View full text |Cite|
|
Sign up to set email alerts
|

Tert-buthylhydroquinone pre-conditioning exerts dual effects in old female rats exposed to 3-nitropropionic acid

Abstract: The brain is a very susceptible organ to structural and functional alterations caused by oxidative stress and its vulnerability increases with age. Understanding the antioxidant response activated by the transcription factor Nrf2 has become very important in the aging field in order to activate cellular protection. However, the role of Nrf2 inducers during old age has not been completely understood. Our aim was to activate the Nrf2 pathway by pre-treating old rats with a widely used Nrf2-inducer, tert-buthylhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 89 publications
0
18
0
3
Order By: Relevance
“…One candidate pathway that may be targeted by drugs is the NRF-2 stress response. In brain tissue, astrocytes are the major cell type to activate this pathway [ 21 , 56 ], and this response may be triggered by pharmacological or non-pharmacological pre-conditioning strategies [ 57 , 58 ]. Stimulation or overexpression of NRF-2 in astrocytes leads to an intracellular GSH increase, to GSH release into the medium and to augmented protection of co-cultured neurons [ 21 , 40 , 41 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…One candidate pathway that may be targeted by drugs is the NRF-2 stress response. In brain tissue, astrocytes are the major cell type to activate this pathway [ 21 , 56 ], and this response may be triggered by pharmacological or non-pharmacological pre-conditioning strategies [ 57 , 58 ]. Stimulation or overexpression of NRF-2 in astrocytes leads to an intracellular GSH increase, to GSH release into the medium and to augmented protection of co-cultured neurons [ 21 , 40 , 41 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenoids and dimethyl fumarate are protective in genetic models of Huntington’s disease, improving survival and motor function and increasing striatal neuron survival [ 212 , 213 ], and curcumin is effective in multiple models of Huntington’s disease [ 214 , 215 , 216 ]. Dimethyl fumarate, CDDO-methylamide, sulforaphane, curcumin nanoparticles, tert-butylhydroquinone, the citrus flavonone naringin, the ginseng extract protopanaxtriol, the organic disulphide cystamine and AI-3 are all protective against 3-nitropropionic acid and decrease striatal lesion size in rats and mice [ 25 , 70 , 207 , 208 , 209 , 211 , 217 , 218 ]. Deletion of Nrf2 abolishes the protective effects of cystamine and tert-butylhydroquinone, confirming the role of Nrf2 in these effects [ 25 , 211 ].…”
Section: Huntington’s Diseasementioning
confidence: 99%
“…3-Nitropropionic acid (3-NPA) irreversibly inhibits the activity of succinate dehydrogenase and promotes ROS formation, thereby inducing oxidative stress [ 13 , 19 ]. Several studies have suggested that 3-NPA significantly increases ROS production in granulosa cells and ovaries and then induces ovarian oxidative damage in mammals [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%